Effects of biological and methodological factors on volatile organic compound patterns during cultural growth of Mycobacterium avium ssp. paratuberculosis. (8th September 2016) - Küntzel, Anne; Fischer, Sina; Bergmann, Andreas; Oertel, Peter; Steffens, Markus; Trefz, Phillip; Miekisch, Wolfram; Schubert, Jochen K; Reinhold, Petra; Köhler, Heike
Abstract: Mycobacterium avium ssp. paratuberculosis (MAP) causes chronic granulomatous enteritis in ruminants. Bacterial growth is still the diagnostic 'gold standard', but is very time consuming. MAP-specific volatile organic compounds (VOCs) above media could accelerate cultural diagnosis. The aim of this project was to assess the kinetics of a VOC profile linked to the growth of MAP in vitro . The following sources of variability were taken into account: five different culture media, three different MAP strains, inoculation with different bacterial counts, and different periods of incubation. Needle-trap microextraction was employed for pre-concentration of VOCs, and gas chromatography–mass spectrometry for subsequent analysis. All volatiles were identified and calibrated by analysing pure references at different concentration levels. More than 100 VOCs were measured in headspaces above MAP-inoculated and control slants. Results confirmed different VOC profiles above different culture media. Emissions could be assigned to either egg-containing media or synthetic ingredients. 43 VOCs were identified as potential biomarkers of MAP growth on Herrold's Egg Yolk Medium without significant differences between the tree MAP strains. Substances belonged to the classes of alcohols, aldehydes, esters, ketones, aliphatic and aromatic hydrocarbons. With increasing bacterial density the VOC concentrations above MAP expressed different patterns: the majority of substances increased (although a few decreased after reaching a peak), but nine VOCs clearly decreased. Data support the hypotheses that (i) bacteria emit different metabolites on different culture media; (ii) different MAP strains show uniform VOC patterns; and (iii) cultural diagnosis can be accelerated by taking specific VOC profiles into account.